A specific problem of mechanism synthesis - Buśkiewicz, Jacek (Zielona Góra: Uniwersytet Zielonogórski)
A technique for path synthesis is employed to design a feeder for carrying products between two points. The feeder is assumed to be a one degree of freedom system of six links connected by means of revolute joints. The mathematical basis of the concept is presented. An exemplary solution is presented and discussed.
Keywords: six-bar linkage; path synthesis; feeder design